2006
DOI: 10.1158/0008-5472.can-05-4386
|View full text |Cite
|
Sign up to set email alerts
|

Apo2l/Tumor Necrosis Factor–Related Apoptosis-Inducing Ligand Prevents Breast Cancer–Induced Bone Destruction in a Mouse Model

Abstract: Breast cancer is the most common carcinoma that metastasizes to bone. To examine the efficacy of recombinant soluble Apo2 ligand (Apo2L)/tumor necrosis factor-related apoptosisinducing ligand (TRAIL) against breast cancer growth in bone, we established a mouse model in which MDA-MB-231 human breast cancer cells were transplanted directly into the marrow cavity of the tibiae of athymic nude mice producing osteolytic lesions in the area of injection. All vehicle-treated control animals developed large lesions th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 31 publications
(50 reference statements)
3
31
0
Order By: Relevance
“…Although TRAIL and an agonistic TRAIL-R2 mAb (Apomab) were previously reported to inhibit bone metastases induced by intratibial injection of breast cancer cells (42,43), our findings are the first to show the antimetastatic activity of TRAIL receptor agonists in an orthotopic model of breast cancer that more faithfully recapitulates the entire metastatic cascade in vivo, including stromal invasion, intravasation, extravasation, and lung colonization. Moreover, our studies are the first direct comparison of the therapeutic efficacy of TRAIL-R1 and TRAIL-R2 agonists in a murine model of breast cancer.…”
Section: Discussionmentioning
confidence: 56%
“…Although TRAIL and an agonistic TRAIL-R2 mAb (Apomab) were previously reported to inhibit bone metastases induced by intratibial injection of breast cancer cells (42,43), our findings are the first to show the antimetastatic activity of TRAIL receptor agonists in an orthotopic model of breast cancer that more faithfully recapitulates the entire metastatic cascade in vivo, including stromal invasion, intravasation, extravasation, and lung colonization. Moreover, our studies are the first direct comparison of the therapeutic efficacy of TRAIL-R1 and TRAIL-R2 agonists in a murine model of breast cancer.…”
Section: Discussionmentioning
confidence: 56%
“…6), consistent with previous findings. 43 Since we also observed that rhApo2L/ TRAIL did not detectably reduce osteoclasts localized to the tumor/bone interface, the reduction in local osteolysis is presumably due to the local reduction in MDA-MB-231 tumor cells in the bone, which would subsequently attenuate the release of observed with either agent alone. We used multiple parameters to assess the efficacy of rhApo2L/TRAIL and RANK-Fc in our skeletal metastasis study, including measurement of tumor observed in the bone microenvironment and not observed in tumors implanted subcutaneously, which, along with the unique effect of RANKL inhibition to reduce osteoclastogenesis, supports the hypothesis that RANK-Fc is disrupting the vicious cycle as observed with previous studies using other RANKL inhibitors.…”
Section: Discussionmentioning
confidence: 61%
“…43,44 We have expanded those findings by demonstrating that rhApo2L/TRAIL combined with muRANK-Fc enhances the reduction in skeletal tumor burden burden by BLI, as well as histopathologic quantitation and X-ray radiography. Based on tumor histology and X-ray lesions (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…5 We have shown that the version of Apo2L/TRAIL that is currently being used in phase 1b clinical trials, inhibited breast cancer growth within bone and protected against cancer-induced osteolysis in a murine model. 6 These results could be explained by the potential of Apo2L/TRAIL to either (1) directly induce apoptosis of breast cancer cells within the bone microenvironment, or, based on the above evidence, (2) block osteoclastogenesis or osteoclast activity via direct inhibitory effects. We have examined in detail the effect of the clinical grade recombinant Apo2L/ TRAIL on bone histology in mice, and also its effect on osteoclast differentiation and bone resorption in 3 independent in vitro models of osteoclastogenesis.…”
Section: Does Apo2l/trail Play Any Physiologic Role In Osteoclastogenmentioning
confidence: 99%